Proof of Concept of Culturomics Use of Time of Care - Naud, Sabrina; Khelaifia, Saber; Mbogning Fonkou, Maxime Descartes; Dione, Niokhor; Lagier, Jean-Christophe; Raoult, Didier (Frontiers in Cellular and Infection Microbiology, 2020)
Culturomics, a high throughput culture method with rapid identification of the colonies by Matrix Assisted Laser Desorption Ionization/Time Of Flight Mass Spectrometry (MALDI-TOF MS), has demonstrated its contribution to the exploration of the gut microbiota over the past 10 years. However, the cost, work time and workload, considerably limit its use on a large scale or emergency context. Here, by testing two different stool samples, including a stool sample from a patient requiring rapid immunotherapy treatment, we tested a new fast culturomic protocol using two pre-incubation media, blood culture bottle and YCFA modified medium. Both media were supplemented with 2 ml of rumen fluid filtered at 0.2 μm and 2 ml of defibrinated and sterile sheep blood. Unlike the standard culturomics, subculturing of blood culture bottle were performed at reduced incubation time (3 h, 6 h, 9 h, 24 h) and at a longer incubation time (3 days, 7 days, and 10 days) at 37°C. By testing 5,200 colonies per MALDI-TOF MS and obtaining a comparable number of cultured bacterial species (131 to 143) in a stool sample, this new protocol reduced the number of colonies tested by 57%, working time by 78.6% and cost by 72.2%. In addition, we highlighted that the proportion of strict anaerobic species has increased by 24%, known to be the preferential targets for biotherapy, including Faecalibacterium prausnitzii, Akkermansia muciniphila, Christensenella minuta, and Phascolarctobacterium faecium. Finally, this work showed that some bacterial species grew earlier but disappeared with prolonged incubation times.